2018
DOI: 10.3390/en11051228
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Flow and Heat Transfer Characteristics in Fractured Granite

Abstract: Hydraulic and heat transfer properties of artificially fractured rocks are the key issues for efficient exploitation of geothermal energy in fractured reservoirs and it has been studied by many previous researchers. However, the fluid temperature evolution along the flow path and rock temperature changes was rarely considered. This study investigated flow and heat transfer characteristics of two sets of fractured granite samples each with a single fissure. The samples were collected from a geothermal reservoir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Figure 2 shows the physical structure model of heat transfer. Luo et al [35,36] analyzed the heat transfer phenomenon in the flow process, and results showed that heat flow is a process of energy exchange. Therefore, the author divides the heat transfer process into three types: linear, curved, and spiral.…”
Section: Causes Of Formation Of High Ground Temperaturementioning
confidence: 99%
“…Figure 2 shows the physical structure model of heat transfer. Luo et al [35,36] analyzed the heat transfer phenomenon in the flow process, and results showed that heat flow is a process of energy exchange. Therefore, the author divides the heat transfer process into three types: linear, curved, and spiral.…”
Section: Causes Of Formation Of High Ground Temperaturementioning
confidence: 99%
“…He et al [13] found that the local heat transfer coefficient (LHTC) distribution mainly depends on the fracture surface roughness, followed by aperture and flow rate. Moreover, Luo et al [14] found that the energy exchange rate increases continuously with the rock temperature, with an effective stress ratio of 1:2. Li et al [15] indicated that the effects of the dissolution reaction on fracture surface morphology exists but it is extremely small for heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…These experiments are useful to quantify heat storage considering the thermal conductivity and specific heat capacity values of groundwater and rock matrices (Molson et al 1992 ; Palmer et al 1992 ; Bridger and Allen 2010 ; Luo et al 2017 ; Dassargues 2018 ; de Schepper et al 2019 ). They allow characterization of the thermal retardation within the medium and to highlight the difference of behavior compared to solute tracers (Geiger and Emmanuel 2010 ; Ma and Zheng 2010 ; Rau et al 2012 ; Irvine et al 2015 , 2017 ; Dassargues 2018 ; de la Bernardie et al 2018 ; Luo et al 2018 ; Sarris et al 2018 ; Hoffmann et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%